Stimulating Students to Speak English Using Oral Games Group Discussion - Sri Fausyia; Andi Muliati; Muh. Tahir (Journal of Excellence in English Language Education, 2022)
The purpose of this study was to find out whether group discussion of oral games improved students' speaking skills. This research was conducted at SMAN 2 Pangkep. The population in this study were students of SMAN 2 Pangkep with samples selected using a simple random sampling technique. The instrument used in this study was a speaking test which was given as a pre-test and post-test. Based on the results of the average score, the researchers found that the use of the technique of describing pictures in stimulating students to speak English using group discussions of oral games could stimulate students to actively speak. This is evidenced by the post-test results which are higher than the pre-test results (25.83 > 53.89). Then, the researcher concluded that describing pictures can stimulate students to speak English by using group discussions of oral games.